Digital twin design requirements in downgraded situations management. Issue 1 (2021) - Dit Pinto, S. Camara; Villeneuve, E.; Masson, D.; Boy, G.; Baron, T.; Urfels, L.
Abstract: The oil-and-gas industry is known to be part of the most safety-critical domains. Safety culture has prompted such companies to implement new systems to support decision-making. In this paper, we explore the use of digital twins to support situation awareness as a crucial part of real-time decisionmaking processes. Therefore, this paper presents requirements for the development of an eight components digital twin. Human-centered approach contributes to add useful information based on user needs and user experience to the usual theoretical process. This user-centered information helped shape both digital twin components and the situation awareness model.